Examining transfer in the acquisition of the count/mass distinction in L2 English. (January 2023) - Tang, Wenting; Fiorentino, Robert; Gabriele, Alison
We investigate whether second language (L2) learners of English rely on first language (L1) transfer and atomicity in the acquisition of the count/mass distinction by examining L1-French and L1-Chinese learners of English. Atomicity encodes whether a noun contains 'atoms' or minimal elements that retain the property of the noun. As a semantic universal, atomicity holds across languages. However, the count/mass status of nouns may differ cross-linguistically. Our results, which show difficulty on atomic mass nouns in both learner groups, support an argument that atomicity is used as a semantic universal in the L2. Our results also suggest that both count/mass status in the L1 and word frequency in the L2 impact performance, suggesting roles for both L1 lexical transfer and lexical frequency. In addition, learners had better performance on abstract as opposed to concrete atomic mass nouns, providing evidence consistent with a theory of the accessibility of atoms.